SOCIO-PSYCHOLOGICAL FOUNDATIONS OF THE APPOINTMENT OF FUTURE OFFICERS TO LEADERSHIP POSITIONS - Shermatov Fayzullo Toshtillaevich (Journals Park Publishing, 2023)
This scientific article indicates that cadets of a Higher military educational institution should be able to manage professional activities, ensure the growth of personnel efficiency and interaction in a military team, as well as carry out the correct selection of superiors and commanders in order to prevent occupational diseases, ensure stable morale of military personnel, investigate their socio-psychological state, motivation to management activities, interaction with the social environment. the ability to engage in communicative communication, scientifically formulated considerations and considerations that the service should have the skills of intellectual activity in the process of data collection and be able to justify the correctness of decisions taken in the management process. Also, scientific research has studied the features of maintaining organizational abilities, emotions, emotions, wrestling activity and emotional endurance in the management process in the necessary dynamics, as well as issues of preparation and implementation of the selection program for practical activities and determining its effectiveness as a research problem. The reliability of the data collected during the study is explained, first of all, by the fact that the subjects who participated in the study were selected accordingly, the practical results obtained were scientifically substantiated, the practical results were analyzed using reliable methods of mathematical statistics of quantitative indicators.
Keywords: leadership in interpersonal relationships, restraint, quick and accurate decision-making in stressful situations, psychological maturity, vigilance, responsiveness, purposefulness, physical maturity, overcoming fear, striving for leadership, perseverance, responsibility, organization, extremity, mental endurance.